Efek Literasi Keuangan Terhadap Minat Berbisnis Menggunakan Model Persamaan Struktural Least Square Parsial - Setia Ningsih; Armayani Arsal (Journal of Principles Management and Business, 2023)
The ability to manage finances can affect one's interest in entrepreneurship. With good financial conditions and knowledge of financial management can improve the business being undertaken. This study aims to determine the effect of financial literacy consisting of financial knowledge, financial behavior and financial attitude on people's interest in entrepreneurship. This research was conducted by conducting a survey of 96 respondents selected using purposive sampling technique and determining the number of samples using the Lemeshow formula. The data collection method uses a questionnaire that is distributed via the Google form. The data analysis technique used is variance-based SEM, namely SEM-PLS. The results of the study show that the variables financial knowledge, financial behavior and financial attitude have a positive and significant impact on people's interest in entrepreneurship with an R-Square value of 76.40%.